2013
DOI: 10.1123/rsj.37.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Collegiate Recreation Participation and Retention

Abstract: Colleges and universities have been focusing on the rising costs to attend college and their impact on current and future students. Recruitment and retention of students is critical in justifying programmatic and academic offerings. In addition, recruitment and retention have an impact on the institution's bottom line. This article attempts to prove a correlation between a collegiate recreation program and retention. Specifically, first year retention rates were examined on students who participate in club spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
71
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(79 citation statements)
references
References 17 publications
(24 reference statements)
3
71
2
3
Order By: Relevance
“…Today, university campuses have become the equivalent to small cities, complete with state-of-the-art recreational facilities, multiple dining facilities, and student unions equipped with coffee shops and storefronts (Dalgarn 2001;June 2006;Lindsey and Sessoms 2006). These resources offer students a myriad of opportunities to meet one another, participate in activities, and immerse themselves in the college experience (Andrijaševic, Ciliga, and Jurakic 2009;Arslan 2013;Artinger et al 2006;Clark and Anderson 2011;Kampf and Teske 2013). These types of recreational activities are considered essential in building a new student's peer circle and connecting them with the college or university (Dalgarn 2001;Kampf and Teske 2013;Rayle and Chung 2007).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Today, university campuses have become the equivalent to small cities, complete with state-of-the-art recreational facilities, multiple dining facilities, and student unions equipped with coffee shops and storefronts (Dalgarn 2001;June 2006;Lindsey and Sessoms 2006). These resources offer students a myriad of opportunities to meet one another, participate in activities, and immerse themselves in the college experience (Andrijaševic, Ciliga, and Jurakic 2009;Arslan 2013;Artinger et al 2006;Clark and Anderson 2011;Kampf and Teske 2013). These types of recreational activities are considered essential in building a new student's peer circle and connecting them with the college or university (Dalgarn 2001;Kampf and Teske 2013;Rayle and Chung 2007).…”
Section: Introductionmentioning
confidence: 98%
“…These resources offer students a myriad of opportunities to meet one another, participate in activities, and immerse themselves in the college experience (Andrijaševic, Ciliga, and Jurakic 2009;Arslan 2013;Artinger et al 2006;Clark and Anderson 2011;Kampf and Teske 2013). These types of recreational activities are considered essential in building a new student's peer circle and connecting them with the college or university (Dalgarn 2001;Kampf and Teske 2013;Rayle and Chung 2007). However, on many campuses partying and associated culture becomes the recreational activity of choice for many students (Allison and Risman 2014;Rhoads 1995;Sanday 2007;Shinew and Parry 2005;Smith and Brown 1998;Weiss 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some universities have health and wellness satellite offices within their SRSCs (e.g., University of New Hampshire's THRIVE) or even have combined departments (e.g., Elon University's Campus Recreation & Wellness). Furthermore, studies have shown that students who use SRSCs have better academic performance and may also remain more connected with the university through continued enrollment (Danbert et al, 2014;Kampf & Teske, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Students participating in university sport experience a number of benefits (Huesman, Brown, Lee, Kellogg, & Radcliffe, 2009;Kampf & Teske, 2013). Despite this, a decrease in participation rates is often found when students enter higher education (Gucciardi & Jackson, 2015).…”
Section: Introductionmentioning
confidence: 99%